Childhood traumatic experiences and mental health problems in sexually offending and non-sexually offending juveniles. Issue 1 (December 2016) - Boonmann, Cyril; Grisso, Thomas; Guy, Laura; Colins, Olivier; Mulder, Eva; Vahl, P.; Jansen, Lucres; Doreleijers, Theo; Vermeiren, Robert
Abstract Objective To examine the relationship between a history of childhood abuse and mental health problems in juveniles who sexually offended (JSOs) over and above general offending behavior. Methods A sample of 44 JSOs incarcerated in two juvenile detention centers in the Netherlands between May 2008 and March 2014 were examined for childhood abuse history (Childhood Trauma Questionnaire-Short Form) and mental health problems (Massachusetts Youth Screening Instrument-Version 2). Furthermore, the connection between childhood abuse and mental health problems in JSOs was compared to a sample of 44 propensity score matched juveniles who offended non-sexually (non-JSOs). Results In JSOs, sexual abuse was related to anger problems, suicidal ideation, and thought disturbance. These associations were significantly stronger in JSOs than in non-JSOs. Conclusions Our results suggest that the relationship between childhood abuse and both internalizing and externalizing mental health problems is of more salience for understanding sexual offending than non-sexual offending, and should, therefore, be an important focus in the assessment and treatment of JSOs.